Models of support to family members during the trajectory of cancer: A scoping review. Issue 21 (10th May 2021) - Samuelsson, Maria; Wennick, Anne; Jakobsson, Jenny; Bengtsson, Mariette
Abstract: Aims and objectives: To map the existing literature on support models provided to family members during the cancer trajectory. Background: Cancer diagnosis, treatment and survivorship have a profound influence on the surrounding family members. This scoping review is part of the development of a support model for family members of persons diagnosed with colorectal cancer. Design: The method was guided by the Arksey and O'Malley framework, described in the Joanna Briggs Institute guidelines, and the reporting is compliant with PRISMA‐ScR Checklist. Searches were conducted in PubMed, CINAHL and PsycINFO from November 2019–February 2020 with no limitation in publication year or study design. Complementing searches were conducted in reference lists and for grey literature, followed by an additional search in September 2020. Inclusion criteria were primary research about support provided by health care, to family members, during cancer, of an adult person, in Swedish or English, of moderate or high methodological quality. Quality was assessed using the Joanna Briggs Institute critical appraisal tools. Data were extracted using a charting form. Result: A total of 32 studies were included in the review describing 39 support models. Conclusion: The mapping of the existing literature resulted in the identification of three themes of support models: psychoeducation, caregiver training and psychological support. In addition, that future research should target a specific diagnosis and trajectory phase as well as include family members and intervention providers in model development. Relevance for clinical practice: Knowledge from the literature on both the needs of the family members and existing support models should be incorporated with the prerequisites of clinical practice. Clinical practice should also be complemented with structured assessments of family members' needs conducted regularly.